2019
DOI: 10.1002/slct.201902950
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Formation of Triphenylborane from Phenylboronic Acid and Its Use as an Intermediate in Palladium‐Catalyzed Cross Coupling Reaction

Abstract: Triphenylborane was unexpectedly formed from phenylboronic acid in the presence of an inorganic base and a polar solvent. When K2CO3 was used as the base and DMF was used as the solvent, 0.22 mmol of triphenylborane was obtained from 1.5 mmol of phenylboronic acid after 1 h at 130 °C. The in‐situ formed triphenylborane reacted with chorobenzene over a supported Pd catalyst to afford biphenyl as the cross coupling product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Motokura et al observed the unexpected formation of triphenylborane (Ph 3 B) during a palladium-catalyzed SM coupling reaction using a mesoporous silica-supported Pd complex catalyst Pd/MS. 44 Ph 3 B is an active intermediate in the SM coupling of aryl chlorides and phenylboronic acids. Meanwhile, Bai et al reported an effective photothermal dual-responsive Pd 1 Cu 4 /Ce x O y catalyst (1 mg/mmol substrate).…”
Section: Suzuki–miyaura Cross-couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Motokura et al observed the unexpected formation of triphenylborane (Ph 3 B) during a palladium-catalyzed SM coupling reaction using a mesoporous silica-supported Pd complex catalyst Pd/MS. 44 Ph 3 B is an active intermediate in the SM coupling of aryl chlorides and phenylboronic acids. Meanwhile, Bai et al reported an effective photothermal dual-responsive Pd 1 Cu 4 /Ce x O y catalyst (1 mg/mmol substrate).…”
Section: Suzuki–miyaura Cross-couplingmentioning
confidence: 99%
“…Motokura et al observed the unexpected formation of triphenylborane (Ph 3 B) during a palladium-catalyzed SM coupling reaction using a mesoporous silica-supported Pd complex catalyst Pd/MS. 44 45 The SM reactions of aryl chlorides and arylboronic acids with this catalyst proceeded under thermal heating at 70 °C. Additionally, SM cross-coupling proceeded under visible-light irradiation at room temperature to afford biaryls in up to 99% yield.…”
Section: Short Review Synthesismentioning
confidence: 99%
See 1 more Smart Citation